2019
DOI: 10.2147/ccid.s195191
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dairy consumption and acne: a case control study in Kabul, Afghanistan</p>

Abstract: Background Previous observational studies suggest that the development of acne may be triggered by dairy intake. Objective This study aimed to investigate the association of dairy intake and acne in Kabul citizens. Methods From February to September 2018, 279 acne patients and 279 controls aged 10–24 years were enrolled in a case control study at the dermatologic outpatient department of Maiwand Teaching Hospital in Kabul City, Afghanistan. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 30 publications
4
26
0
5
Order By: Relevance
“…Three studies also suggested that milk intake may increase the risk of more severe acne [40][41][42] , which is consistent with a meta-analysis that reported that high milk consumption was significantly associated with the presentation of moderate-severe acne 43 . Explanations for the association between milk intake and acne presentation may also explain the association observed for milk intake and acne severity.…”
Section: Parameters That Differ Between Control and Casesupporting
confidence: 80%
“…Three studies also suggested that milk intake may increase the risk of more severe acne [40][41][42] , which is consistent with a meta-analysis that reported that high milk consumption was significantly associated with the presentation of moderate-severe acne 43 . Explanations for the association between milk intake and acne presentation may also explain the association observed for milk intake and acne severity.…”
Section: Parameters That Differ Between Control and Casesupporting
confidence: 80%
“…The majority of case‐control studies evaluated the link between acne and dietary pattern 15‐30 and one the effects of the consumption of dairy products 31 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…assessed a study on late adolescents, showing that frequent consumption (≥3 days per week) of dairy products, chocolate, and other dietary items (i.e. eggs, potato chips, pizza/bolani) was statistically associated with moderate to severe acne 24 . In Kazakhstan, Tsoy et al .…”
Section: Resultsmentioning
confidence: 99%
“…High glycemic load diet can lead to the rise in blood glucose in the body, therefore, islets secrete large amounts of insulin to lower blood glucose, and elevated insulin levels lead to increased secretion of insulin-like growth factors-1 (IGF-1), IGF-1 can increase androgen levels, promote sebum secretion, and promote hyperkeratosis of hair follicle sebaceous glands to affect lipid excretion, thereby inducing or aggravating the occurrence of acne ( 53 56 ). And there were studies about a positive association between the incidence of acne and the intake of whole milk and skim milk ( 57 , 58 ). Milk can also increase the level of IGF-1, which can lead to acne ( 47 , 59 61 ).…”
Section: Resultsmentioning
confidence: 99%